2005
DOI: 10.1037/0097-7403.31.2.142
|View full text |Cite
|
Sign up to set email alerts
|

What Do Rats Learn About the Geometry of Object Arrays? Tests With Exploratory Behavior.

Abstract: Six experiments using habituation of exploratory behavior tested whether disoriented rats foraging in a large arena encode the shapes of arrays of objects. Rats did not respond to changes in position of a single object, but they responded to a change in object color and to a change in position of 1 object in a square array, as in previous research (e.g., C. Thinus-Blanc et al., 1987). Rats also responded to an expansion of a square array, suggesting that they encoded sets of interobject distances rather than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
1
9
1
Order By: Relevance
“…According to the geometric module concept, rats in the present study should similarly perceive the structure of an equispaced square array of four objects in a small (1 × 1 m) or in a large (2 × 2 m) arena, since both comprise the same geometry and differ only in the distance between objects. Perceiving geometric shape was previously demonstrated in hamsters [39] but not in rats [40]; however, the present results support the encoding of a geometric module by rats, since when exposed to 'elastic' expansion of an arena they preserved the same overall preference for certain objects that they had had before arena expansion (Figure 3). The results obtained here follow the prediction of Jacobs and Schenk [27], suggesting that " a given sketch will be recognized as such in spite of changes in size, although this might induce a general activity response ".…”
Section: Discussionsupporting
confidence: 50%
“…According to the geometric module concept, rats in the present study should similarly perceive the structure of an equispaced square array of four objects in a small (1 × 1 m) or in a large (2 × 2 m) arena, since both comprise the same geometry and differ only in the distance between objects. Perceiving geometric shape was previously demonstrated in hamsters [39] but not in rats [40]; however, the present results support the encoding of a geometric module by rats, since when exposed to 'elastic' expansion of an arena they preserved the same overall preference for certain objects that they had had before arena expansion (Figure 3). The results obtained here follow the prediction of Jacobs and Schenk [27], suggesting that " a given sketch will be recognized as such in spite of changes in size, although this might induce a general activity response ".…”
Section: Discussionsupporting
confidence: 50%
“…Our finding that geometric cues by themselves have only a weak influence on HD cell orientation seems surprising given the substantial behavioral literature suggesting a primacy for geometric cues over landmarks (Cheng, 1986; see Cheng and Newcombe, 2005 for review). However, most behavioral studies have been undertaken in disoriented rats (e.g., Maes et al, 2009;Gibson et al, 2007;Cheng and Gallistel, 2005;Skov-Rackette and Shettleworth, 2005;Wall et al, 2004;Maurer and Derivaz, 2000;Cheng, 1986s) in which path integration has been disrupted. The present results suggest that geometric cues are able to influence HD cells if other sources of orienting information are absent.…”
Section: Discussionmentioning
confidence: 99%
“…There was a suggestion (Benhamou & Poucet, ) that the perception of geometry can be created by arranging local objects in a particular geometrical configuration. However other studies suggest that this is not the case (Skov‐Rackette & Shettleworth, ). It has been shown that the rotation of local objects arranged in a triangular layout had little control over place fields (Cressant et al .…”
Section: Introductionmentioning
confidence: 94%